Real-time continuous glucose monitoring-guided glucose management in inpatients with diabetes receiving short-term continuous subcutaneous insulin infusion: a randomized clinical trialResearch in context - Yaxin Wang; Jingyi Lu; Ming Wang; Jiaying Ni; Jiamin Yu; Shiyun Wang; Liang Wu; Wei Lu; Wei Zhu; Jingyi Guo; Xiangtian Yu; Yuqian Bao; et al. (Elsevier, 2024)
Summary: Background: The use of real-time continuous glucose monitoring (rtCGM) technology remains largely investigational in the hospital setting. The current study aimed to evaluate the effectiveness of rtCGM in inpatients with diabetes who were treated with short-term continuous subcutaneous insulin infusion (CSII). Methods: In this randomized, parallel controlled trial conducted on the endocrinology wards in a tertiary hospital located in Shanghai, adults with type 1 and type 2 diabetes who required short-term CSII during hospitalization were randomly assigned (1:1) to receive either rtCGM-based glucose monitoring and management program or point-of-care (POC) standard of care (8 times/day) with blinded CGM. Primary outcome measure was the difference in the percentage of time within the target glucose range of 3.9-10 mmol/L (TIR, %). This study was registered at www.chictr.org.cn (ChiCTR2300068933). Findings: Among the 475 randomized participants (237 in the rtCGM group and 238 in the POC group), the mean age of was 60 ± 13 years, and the mean baseline glycated hemoglobin level was 9.4 ± 1.8%. The CGM-recorded mean TIR was 71.1 ± 15.8% in the rtCGM group and 62.9 ± 18.9% in the POC group, with a mean difference of 8.2% (95% confidence interval [CI]: 5.1-11.4%, P < 0.001). The mean time above range >10 mmol/L was significantly lower in the rtCGM group than in the POC group (28.3 ± 15.8% vs. 36.6 ± 19.0%, P < 0.001), whereas there was no significant between-group difference in the time below range <3.9 mmol/L (P = 0.11). Moreover, the time to reach target glucose was significantly shorter in the rtCGM group than in the POC group (2.0 [1.0-4.0] days vs. 4.0 [2.0-5.0] days, P < 0.001). There were no serious adverse events in both groups. Interpretation: In patients with diabetes who received short-term CSII during hospitalization, the rtCGM program resulted in better glucose control than the POC standard of care, without increasing the risk of hypoglycemia. Funding: The Program of Shanghai Academic Research Leader (22XD1402300), Shanghai Oriental Talent Program (Youth Project) (No. NA), the Shanghai "Rising Stars of Medical Talent" Youth Development Program-Outstanding Youth Medical Talents (SHWSRS(2021)_099), and the Shanghai Research Center for Endocrine and Metabolic Diseases (2022ZZ01002).